Fairness in Bankruptcies: An Experimental Study - Cappelen, Alexander W.; Luttens, Roland Iwan; Sørensen, Erik Ø.; Tungodden, Bertil (Management Science, 2019)
The pari passu principle of awarding claimants proportionally to their pre-insolvency claims is the most prominent principle in the law of insolvency. We report from a lab experiment designed to study whether people find this principle a fair solution to the bankruptcy problem. The experimental design generates situations where participants work and accumulate claims in firms, some of which subsequently go bankrupt. Third-party arbitrators are randomly assigned to determine how the liquidation value of the bankrupt firms should be distributed between claimants. Our main finding is that there is a striking support for the pari passu principle. We estimate a random utility model that allows for the arbitrators to differ in what they consider a fair solution to the bankruptcy problem and find that about 85% of the participants endorse the proportional rule. We also find that a nonnegligible fraction of the arbitrators follow the constrained equal losses rule, while there is almost no support in our experiment for the constrained equal awards rule or other fairness rules suggested in the normative literature. Data and the online appendix are available at https://doi.org/10.1287/mnsc.2018.3029 . This paper was accepted by David Simchi-Levi, behavioral economics.